Atomization of As and Se volatile species in a dielectric barrier discharge atomizer after hydride generation: Fate of analyte studied by selected ion flow tube mass spectrometry - Kratzer, Jan; Lacko, Michal; Dryahina, Kseniya; Matoušek, Tomáš; Španěl, Patrik; Dědina, Jiří (Analytica chimica acta, 2022)
Atomization of hydrides and their methylated analogues in a dielectric barrier discharge (DBD) plasma atomizer was investigated. Selected ion flow tube mass spectrometry (SIFT-MS) was chosen as a detector being capable of selective detection of non-atomized original volatile species allowing thus direct quantification of atomization efficiency. Selenium hydride (SeH2) and three volatile arsenic species, namely arsenic hydride (AsH3), monomethylarsane (CH3AsH2) and dimethylarsane ((CH3)2AsH), were selected as model analytes. The mechanistic study performed contributes to understanding of the atomization processes in atomic absorption spectrometry (AAS). The presented results are compatible with a complete atomization of arsenic hydride as well as its methylated analogues and with atomization efficiency of SeH2 below 80%. Using AsH3 as a model analyte and a combination of AAS and SIFT-MS detectors has revealed that the hydride is not atomized, but decomposed in the DBD atomizer in absence of hydrogen fraction in the carrier gas. Apart from investigation of analyte atomization, the SIFT-MS detector is capable of quantitative determination of water vapor content being either transported to, or produced in the atomizer. This information is crucial especially in the case of the low-power/temperature DBD atomizer since its performance is sensitive to the amount of water vapor introduced into the plasma.
Keywords: Mass Spectrometry; Spectrophotometry, Atomic; vodík; Nebulizers and Vaporizers; spektrofotometrie atomová; Hydrogen; hmotnostní spektrometrie; Arsenic; nebulizátory a vaporizátory; arsen